Effect of weight-bearing in bicruciate-retaining total knee arthroplasty during high-flexion activities. (February 2022) - Kono, Kenichi; Inui, Hiroshi; Tomita, Tetsuya; Yamazaki, Takaharu; Taketomi, Shuji; Yamagami, Ryota; Kawaguchi, Kohei; Kage, Tomofumi; Arakawa, Takahiro; Tanaka, Sakae
Abstract: Background: To evaluate the effect of weight-bearing on the kinematics of the bicruciate-retaining total knee arthroplasty design during high knee flexion activities. Methods: The kinematics of 21 bicruciate-retaining total knee arthroplasties were evaluated under fluoroscopy, with two- and three-dimensional image registrations, during squatting (weight-bearing) and active-assisted knee flexion (non-weight-bearing). The following variables were measured: knee range of motion, axis of femoral rotation and varus-valgus angle relative to the tibial component, anteroposterior translation of the medial and lateral contact points, and the kinematic pathway of the joint surfaces. Findings: From 20° to 100° of flexion, the femoral external rotation during weight-bearing was larger than that during non-weight-bearing. There were no differences in the varus-valgus angles between the two conditions. From 10° to 50° of flexion, the medial contact point during weight-bearing was located posterior to the point of contact during non-weight-bearing; this difference between the two weight-bearing conditions was significant. From 0° to 90° of flexion, the lateral contact point in weight-bearing was located posterior to the contact point in non-weight-bearing; this difference between the two weight-bearing conditions was also significant. Interpretation: The anteroposterior position of the medial and lateral contact points of the bicruciate-retaining total knee arthroplasty design was significantly more posterior in the mid-range of knee flexion in weight-bearing than in non-weight-bearing. However, no anterior translation of the bicruciate-retaining total knee arthroplasty design was observed. Therefore, bicruciate-retaining total knee arthroplasty appears to have good anteroposterior stability throughout the range of knee flexion, regardless of the weight-bearing condition. Highlights: We analyzed bicruciate-retaining total knee arthroplasty kinematics. Weight-bearing and non-weight-bearing conditions were studied. Anteroposterior contact points were more posterior with mid-range knee flexion. However, no anterior translation was observed.